A Role of Calcium Signaling Genes in Heterokaryon Incompatibility in Neurospora crassa - Gedela, Ravi; Tamuli, Ranjan (International Journal of Applied Sciences and Biotechnology, 2015)
We have studied the Ca2+-signaling knockout mutants for their role in mating-type-associated heterokaryon incompatibility in Neurospora crassa. The found results showed on heterokaryons homokaryosis for DNCU05225, DNCU06366, DNCU06650, DNCU07075, and ∆NCU07966 Ca2+-signaling knockout mutants (Neurospora crassa unit number, NCU) displayed heterokaryon het compatibility; however heterokaryons heterokaryosis for DNCU05225, DNCU063665, DNCU06650, DNCU07075, and ∆NCU07966 mutants displayed het incompatibility like the wild-type control. In addition to that Two Ca2+-signaling knockout mutants DNCU02283, and DNCU09655 were tested for mating-type-associated heterokaryon incompatibility; these results showed, heterokaryons homokaryosis and heterokaryons heterokaryosis for DNCU02283, DNCU09655 mutants displayed het incompatibility. Cell death and hyphal compartmentation due to mating type associated incompatibility were confirmed by uptake of vital dye Evan’s blue. Thus, these results of NCU05225, NCU06366, NCU06650, NCU07075, and NCU07966 Ca2+-signaling gene products could play a role in mating-type-associated heterokaryon incompatibility in N. crassa. In this article, we are reporting initially screened Ca2+-signaling gene deletion mutants of these five acts as recessive suppressors of mating type associated vegetative incompatibility in N. crassa. Int J Appl Sci Biotechnol, Vol 3(4): 668-679